Integrated genomic analysis reveals actionable targets in pediatric spinal cord low-grade gliomas - Misove, Adela; Vicha, Ales; Broz, Petr; Vanova, Katerina; Sumerauer, David; Stolova, Lucie; Sramkova, Lucie; Koblizek, Miroslav; Zamecnik, Josef; Kyncl, Martin; Holubova, Zuzana; Liby, Petr; et al. (Acta neuropathologica communications, 2022)
Gliomas are the most common central nervous tumors in children and adolescents. However, spinal cord low-grade gliomas (sLGGs) are rare, with scarce information on tumor genomics and epigenomics. To define the molecular landscape of sLGGs, we integrated clinical data, histology, and multi-level genetic and epigenetic analyses on a consecutive cohort of 26 pediatric patients. Driver molecular alteration was found in 92% of patients (24/26). A novel variant of KIAA1549:BRAF fusion (ex10:ex9) was identified using RNA-seq in four cases. Importantly, only one-third of oncogenic drivers could be revealed using standard diagnostic methods, and two-thirds of pediatric patients with sLGGs required extensive molecular examination. The majority (23/24) of detected alterations were potentially druggable targets. Four patients in our cohort received targeted therapy with MEK or NTRK inhibitors. Three of those exhibited clinical improvement (two with trametinib, one with larotrectinib), and two patients achieved partial response. Methylation profiling was implemented to further refine the diagnosis and revealed intertumoral heterogeneity in sLGGs. Although 55% of tumors clustered with pilocytic astrocytoma, other rare entities were identified in this patient population. In particular, diffuse leptomeningeal glioneuronal tumors (n = 3) and high-grade astrocytoma with piloid features (n = 1) and pleomorphic xanthoastrocytoma (n = 1) were present. A proportion of tumors (14%) had no match with the current version of the classifier. Complex molecular genetic sLGGs characterization was invaluable to refine diagnosis, which has proven to be essential in such a rare tumor entity. Moreover, identifying a high proportion of drugable targets in sLGGs opened an opportunity for new treatment modalities.
Keywords: nádory mozku; Humans; Brain Neoplasms; Proto-Oncogene Proteins B-raf; dítě; Child; genomika; mitogenem aktivované proteinkinasy kinas; lidé; Astrocytoma; protoonkogenní proteiny B-raf; Mitogen-Activated Protein Kinase Kinases; Adolescent; gliom; nádory míchy; astrocytom; Genomics; Spinal Cord Neoplasms; Glioma; mladiství